Infrastructure Project Financing Options: Traditional and New Sources, Strategies for Avoiding Dutch Disease, China’s White Knight Interventions, and the U.S. BUILD Act (2018) for Sustainable Development - Susan S., Nash, (IJRDO - Journal of Social Science and Humanities Research, 2018)
Infrastructure development is vital for economic and human capacity development of a nation. And yet, many times financing is difficult to obtain, particularly in the areas that need it most.  Ironically, some of the countries that have recent discoveries of oil, gas, and valuable minerals, and seem most able to pay off potential loans, have not had access to financing, or it has come in ways that do not stimulate economic development across the economy, but instead lead to the economic illnesses associated with the Paradox of Plenty, such as Dutch Disease. Traditional sources have been wary of lending to such nations due to their poor credit scores, lack of transparency, or human rights issues. New sources of infrastructure investment, such as China’s multi-trillion Belt and Road Initiative, have functioned as a “white knight” in providing infrastructure to achieve an expansion and deepening of trade relationships. For optimal economic impact, it is important to couple the infrastructure with companies that can establish local businesses that create a solid domestic value chain, and which fill gaps in the supply chain. The U.S. BUILD Act, passed in 2018, which establishes the new International Development Finance Corporation (IDFC) will provide loans for business-to-business projects involving local companies and U.S. companies. Such financing could assist countries in achieving sustainable development, avoid the Dutch Disease, and successfully repay their infrastructure loans.